Haskell implementation of rb-j's IIR cookbook. I have turned his text
file into a literate Haskell file. You can find the original at:
http://www.harmony-central.com/Computer/Programming/Audio-EQ-Cookbook.txt
--Matt Donadio (m.p.donadio@ieee.org)
> -----------------------------------------------------------------------------
> -- |
> -- Module : DSP.Filter.IIR.IIR
> -- Copyright : (c) Matthew Donadio 2003
> -- License : GPL
> --
> -- Maintainer : m.p.donadio@ieee.org
> -- Stability : experimental
> -- Portability : portable
> --
> -- Cookbook formulae for audio EQ biquad filter coefficients
> -- by Robert Bristow-Johnson
> --
> --
> --
> -----------------------------------------------------------------------------
> module DSP.Filter.IIR.Cookbook where
> import DSP.Filter.IIR.IIR
Cookbook formulae for audio EQ biquad filter coefficients
-----------------------------------------------------------------------------
by Robert Bristow-Johnson
All filter transfer functions were derived from analog prototypes (that
are shown below for each EQ filter type) and had been digitized using the
Bilinear Transform. BLT frequency warping has been taken into account
for both significant frequency relocation and for bandwidth readjustment.
First, given a biquad transfer function defined as:
b0 + b1*z^-1 + b2*z^-2
H(z) = ------------------------ (Eq 1)
a0 + a1*z^-1 + a2*z^-2
This shows 6 coefficients instead of 5 so, depending on your
architechture, you will likely normalize a0 to be 1 and perhaps also
b0 to 1 (and collect that into an overall gain coefficient). Then
your transfer function would look like:
(b0/a0) + (b1/a0)*z^-1 + (b2/a0)*z^-2
H(z) = --------------------------------------- (Eq 2)
1 + (a1/a0)*z^-1 + (a2/a0)*z^-2
or
1 + (b1/b0)*z^-1 + (b2/b0)*z^-2
H(z) = (b0/a0) * --------------------------------- (Eq 3)
1 + (a1/a0)*z^-1 + (a2/a0)*z^-2
The most straight forward implementation would be the Direct I form
(using Eq 2):
y[n] = (b0/a0)*x[n] + (b1/a0)*x[n-1] + (b2/a0)*x[n-2]
- (a1/a0)*y[n-1] - (a2/a0)*y[n-2] (Eq 4)
This is probably both the best and the easiest method to implement in
the 56K.
Now, given:
sampleRate (the sampling frequency)
frequency ("wherever it's happenin', man." "center" frequency
or "corner" (-3 dB) frequency, or shelf midpoint frequency,
depending on which filter type)
dBgain (used only for peaking and shelving filters)
bandwidth in octaves (between -3 dB frequencies for BPF and notch
or between midpoint (dBgain/2) gain frequencies for peaking EQ)
_or_ Q (the EE kind of definition, except for peakingEQ in which A*Q
is the classic EE Q. That adjustment in definition was done so
that a boost of N dB followed by a cut of N dB for identical Q and
frequency results in a perfectly flat unity gain filter or "wire".)
_or_ S, a "shelf slope" parameter (for shelving EQ only). When S = 1,
the shelf slope is as steep as it can be and remain monotonically
increasing or decreasing gain with frequency. The shelf slope, in
dB/octave, remains proportional to S for all other values.
First compute a few intermediate variables:
A = sqrt[ 10^(dBgain/20) ]
= 10^(dBgain/40) (for peaking and shelving EQ filters only)
omega = 2*pi*frequency/sampleRate
sin = sin(omega)
cos = cos(omega)
alpha = sin/(2*Q) (if Q is specified)
= sin*sinh[ ln(2)/2 * bandwidth * omega/sin ] (if bandwidth is specified)
The relationship between bandwidth and Q is
1/Q = 2*sinh[ln(2)/2*bandwidth*omega/sin] (digital filter using BLT)
or 1/Q = 2*sinh[ln(2)/2*bandwidth]) (analog filter prototype)
beta = sqrt(A)/Q (for shelving EQ filters only)
= sqrt(A)*sqrt[ (A + 1/A)*(1/S - 1) + 2 ] (if shelf slope is specified)
= sqrt[ (A^2 + 1)/S - (A-1)^2 ]
The relationship between shelf slope and Q is
1/Q = sqrt[(A + 1/A)*(1/S - 1) + 2]
Then compute the coefficients for whichever filter type you want:
The analog prototypes are shown for normalized frequency.
The bilinear transform substitutes:
1 1 - z^-1
s <- -------------- * ----------
tan(omega/2) 1 + z^-1
and makes use of these trig identities:
sin(w) 1 - cos(w)
tan(w/2) = ------------ (tan(w/2))^2 = ------------
1 + cos(w) 1 + cos(w)
LPF: H(s) = 1 / (s^2 + s/Q + 1)
b0 = (1 - cos)/2
b1 = 1 - cos
b2 = (1 - cos)/2
a0 = 1 + alpha
a1 = -2*cos
a2 = 1 - alpha
> {-# specialize lpf :: Float -> Float -> [Float] -> [Float] #-}
> {-# specialize lpf :: Double -> Double -> [Double] -> [Double] #-}
> lpf :: Floating a => a -> a -> [a] -> [a]
> lpf bw w = biquad_df1 (a1/a0) (a2/a0) (b0/a0) (b1/a0) (b2/a0)
> where b0 = (1 - cos w) / 2
> b1 = 1 - cos w
> b2 = (1 - cos w) / 2
> a0 = 1 + alpha
> a1 = -2 * cos w
> a2 = 1 - alpha
> alpha = sin w * sinh (log 2 / 2 * bw * w / sin w)
HPF: H(s) = s^2 / (s^2 + s/Q + 1)
b0 = (1 + cos)/2
b1 = -(1 + cos)
b2 = (1 + cos)/2
a0 = 1 + alpha
a1 = -2*cos
a2 = 1 - alpha
> {-# specialize hpf :: Float -> Float -> [Float] -> [Float] #-}
> {-# specialize hpf :: Double -> Double -> [Double] -> [Double] #-}
> hpf :: Floating a => a -> a -> [a] -> [a]
> hpf bw w = biquad_df1 (a1/a0) (a2/a0) (b0/a0) (b1/a0) (b2/a0)
> where b0 = (1 + cos w) / 2
> b1 = -(1 + cos w)
> b2 = (1 + cos w) / 2
> a0 = 1 + alpha
> a1 = -2 * cos w
> a2 = 1 - alpha
> alpha = sin w * sinh (log 2 / 2 * bw * w / sin w)
BPF: H(s) = s / (s^2 + s/Q + 1) (constant skirt gain, peak gain = Q)
b0 = sin/2 = Q*alpha
b1 = 0
b2 = -sin/2 = -Q*alpha
a0 = 1 + alpha
a1 = -2*cos
a2 = 1 - alpha
> {-# specialize bpf_csg :: Float -> Float -> [Float] -> [Float] #-}
> {-# specialize bpf_csg :: Double -> Double -> [Double] -> [Double] #-}
> bpf_csg :: Floating a => a -> a -> [a] -> [a]
> bpf_csg bw w = biquad_df1 (a1/a0) (a2/a0) (b0/a0) (b1/a0) (b2/a0)
> where b0 = sin w / 2
> b1 = 0
> b2 = -sin w / 2
> a0 = 1 + alpha
> a1 = -2 * cos w
> a2 = 1 - alpha
> alpha = sin w * sinh (log 2 / 2 * bw * w / sin w)
BPF: H(s) = (s/Q) / (s^2 + s/Q + 1) (constant 0 dB peak gain)
b0 = alpha
b1 = 0
b2 = -alpha
a0 = 1 + alpha
a1 = -2*cos
a2 = 1 - alpha
> {-# specialize bpf_cpg :: Float -> Float -> [Float] -> [Float] #-}
> {-# specialize bpf_cpg :: Double -> Double -> [Double] -> [Double] #-}
> bpf_cpg :: Floating a => a -> a -> [a] -> [a]
> bpf_cpg bw w = biquad_df1 (a1/a0) (a2/a0) (b0/a0) (b1/a0) (b2/a0)
> where b0 = alpha
> b1 = 0
> b2 = -alpha
> a0 = 1 + alpha
> a1 = -2 * cos w
> a2 = 1 - alpha
> alpha = sin w * sinh (log 2 / 2 * bw * w / sin w)
notch: H(s) = (s^2 + 1) / (s^2 + s/Q + 1)
b0 = 1
b1 = -2*cos
b2 = 1
a0 = 1 + alpha
a1 = -2*cos
a2 = 1 - alpha
> {-# specialize notch :: Float -> Float -> [Float] -> [Float] #-}
> {-# specialize notch :: Double -> Double -> [Double] -> [Double] #-}
> notch :: Floating a => a -> a -> [a] -> [a]
> notch bw w = biquad_df1 (a1/a0) (a2/a0) (b0/a0) (b1/a0) (b2/a0)
> where b0 = 1
> b1 = -2 * cos w
> b2 = 1
> a0 = 1 + alpha
> a1 = -2 * cos w
> a2 = 1 - alpha
> alpha = sin w * sinh (log 2 / 2 * bw * w / sin w)
APF: H(s) = (s^2 - s/Q + 1) / (s^2 + s/Q + 1)
b0 = 1 - alpha
b1 = -2*cos
b2 = 1 + alpha
a0 = 1 + alpha
a1 = -2*cos
a2 = 1 - alpha
> {-# specialize apf :: Float -> Float -> [Float] -> [Float] #-}
> {-# specialize apf :: Double -> Double -> [Double] -> [Double] #-}
> apf :: Floating a => a -> a -> [a] -> [a]
> apf bw w = biquad_df1 (a1/a0) (a2/a0) (b0/a0) (b1/a0) (b2/a0)
> where b0 = 1 - alpha
> b1 = -2 * cos w
> b2 = 1 + alpha
> a0 = 1 + alpha
> a1 = -2 * cos w
> a2 = 1 - alpha
> alpha = sin w * sinh (log 2 / 2 * bw * w / sin w)
peakingEQ: H(s) = (s^2 + s*(A/Q) + 1) / (s^2 + s/(A*Q) + 1)
b0 = 1 + alpha*A
b1 = -2*cos
b2 = 1 - alpha*A
a0 = 1 + alpha/A
a1 = -2*cos
a2 = 1 - alpha/A
> {-# specialize peakingEQ :: Float -> Float -> Float -> [Float] -> [Float] #-}
> {-# specialize peakingEQ :: Double -> Double -> Double -> [Double] -> [Double] #-}
> peakingEQ :: Floating a => a -> a -> a -> [a] -> [a]
> peakingEQ bw dBgain w = biquad_df1 (a1/a0) (a2/a0) (b0/a0) (b1/a0) (b2/a0)
> where b0 = 1 + alpha * a
> b1 = -2 * cos w
> b2 = 1 - alpha * a
> a0 = 1 + alpha / a
> a1 = -2 * cos w
> a2 = 1 - alpha / a
> alpha = sin w * sinh (log 2 / 2 * bw * w / sin w)
> a = 10 ** (dBgain / 40)
lowShelf: H(s) = A * (s^2 + (sqrt(A)/Q)*s + A) / (A*s^2 + (sqrt(A)/Q)*s + 1)
b0 = A*[ (A+1) - (A-1)*cos + beta*sin ]
b1 = 2*A*[ (A-1) - (A+1)*cos ]
b2 = A*[ (A+1) - (A-1)*cos - beta*sin ]
a0 = (A+1) + (A-1)*cos + beta*sin
a1 = -2*[ (A-1) + (A+1)*cos ]
a2 = (A+1) + (A-1)*cos - beta*sin
> {-# specialize lowShelf :: Float -> Float -> Float -> Float -> [Float] -> [Float] #-}
> {-# specialize lowShelf :: Double -> Double -> Double -> Double -> [Double] -> [Double] #-}
> lowShelf :: Floating a => a -> a -> a -> a -> [a] -> [a]
> lowShelf bw s dBgain w = biquad_df1 (a1/a0) (a2/a0) (b0/a0) (b1/a0) (b2/a0)
> where b0 = a*( (a+1) - (a-1) * cos w + beta * sin w)
> b1 = 2*a*( (a-1) - (a+1) * cos w )
> b2 = a*( (a+1) - (a-1) * cos w - beta * sin w)
> a0 = (a+1) + (a-1) * cos w + beta * sin w
> a1 = -2*( (a-1) + (a+1) * cos w )
> a2 = (a+1) + (a-1) * cos w - beta * sin w
> beta = sqrt ((a^2 + 1) / s - (a-1)^2)
> a = 10 ** (dBgain / 40)
highShelf: H(s) = A * (A*s^2 + (sqrt(A)/Q)*s + 1) / (s^2 + (sqrt(A)/Q)*s + A)
b0 = A*[ (A+1) + (A-1)*cos + beta*sin ]
b1 = -2*A*[ (A-1) + (A+1)*cos ]
b2 = A*[ (A+1) + (A-1)*cos - beta*sin ]
a0 = (A+1) - (A-1)*cos + beta*sin
a1 = 2*[ (A-1) - (A+1)*cos ]
a2 = (A+1) - (A-1)*cos - beta*sin
> {-# specialize highShelf :: Float -> Float -> Float -> Float -> [Float] -> [Float] #-}
> {-# specialize highShelf :: Double -> Double -> Double -> Double -> [Double] -> [Double] #-}
> highShelf :: Floating a => a -> a -> a -> a -> [a] -> [a]
> highShelf bw s dBgain w = biquad_df1 (a1/a0) (a2/a0) (b0/a0) (b1/a0) (b2/a0)
> where b0 = a*( (a+1) - (a-1) * cos w + beta * sin w)
> b1 = -2*a*( (a-1) - (a+1) * cos w )
> b2 = a*( (a+1) - (a-1) * cos w - beta * sin w)
> a0 = (a+1) + (a-1) * cos w + beta * sin w
> a1 = -2*( (a-1) + (a+1) * cos w )
> a2 = (a+1) + (a-1) * cos w - beta * sin w
> beta = sqrt ((a^2 + 1) / s - (a-1)^2)
> a = 10 ** (dBgain / 40)
(This text-only file is best viewed or printed with a mono-spaced font.)